EKTRAK KULIT MANGGIS (Garcinia Mangostana L) SEBAGAI ALTERNATIF PENGGANTI EOSIN UNTUK PEMERIKSAAN TELUR CACING - Apriani Apriani; Ereskadi Ereskadi (Asosiasi Institusi Pendidikan Tinggi Teknologi Laboratorium Medik Indonesia, 2022)
Direct examination of worm eggs was found to be colorless, making it difficult to see under a microscope. The use of Eosin 2% is a simple method of examining worm eggs commonly used in medical diagnosis and research. Some of the drawbacks of Eosin are high price and its ingredients can damage the environment. Another dye to consider is the mangosteen peel. Mangosteen peel contains anthocyanins which produce a red color. This study aims to see whether mangosteen peel (Garcinia mangostana L) can be used as an alternative for coloring intestinal nematode worm eggs. This study used a descriptive experimental method, namely observation by looking at the contrast, color absorption, and clarity of the egg in the microscope. The concentration used in this study were 1:1; 1:2; 1:3; 1:4 and 1:5. Staining using mangosteen peel (Garcinia mangostana L) at a concentration (1: 2) showed the quality of the staining was close to the quality of the 2% eosin staining (control). This makes mangosteen peel extract (Garcinia mangostana L) can be used as an alternative to eosin in examining worm eggs.